World drug report (Oxford Univ. P. OxfordGB, 1997)
Provides a global overview of recent patterns and trends in illict drug production, trafficking and consumption. Looks at the range of theories put forward to explain why people take drugs. Studies the effects of drugs on the human organism and the social impact on individuals, families and communities. Discusses the consequences of the illegal drug economy at the national and international level. Focuses on the role and responsibilities of national and international bodies in tackling the spectrum of drug problems, and the strategies used to reduce the demand for, and supply of, illict drugs. Looks at the drug problems of eight 'core countries'.
DC